Problem of the protection of the edible dormouse species (Glis glis L.) in Poland - Terlecka, Magdalena Klaudia (Studia Ecologiae et Bioethicae, 2010)
Coming conclusions from this study are inducing to formulating the statement, that leading to the next controlled and thought reintroductions programs and protections of the Glis glis kind in Poland is necessary. Also conducting accurate examinations and the monitoring of the population of the edible dormouse should be a big challenge. It is also necessary raising qualifications of the employees of National Forests responsible for the protection of kinds and conducting the environmental education of the society which will be aimed at demonstrating, easily it is possible to protect the edible dormouse and how it is important for her more further existing in Polish forests. Without the practical protection of natural settlements of the edible dormouse regulations legislative, guaranteeing her the protection (Bern Convention, entry to the IUCN list, Polish acts and regulations) aren’t playing a significant role. The edible dormouse is happening to make its way oneself with a very powerful enemy, with which unfortunately he isn’t having a chance to the win – with a man. The man is just transforming the environment of Glis glis species depriving him of settlements, foods, hunting it, but simultaneously the man is passing attempts of the protection and programs of the reintroduction. We can happen or the vanquisher or the savior of the edible dormouse species. The choice depends only on us.